Energy transmission processes in the effectuation chain of solar forcing to the terrestrial atmosphere—a review - Wang, Jingsong; Zhao, Liang; Xiao, Ziniu; Zhang, Peng; Ren, Zhipeng; Zong, Weiguo; Qi, Jin; Huang, Cong; Xu, Ying; Lu, Yixiong (Frontiers in Earth Science, 2023)
The Sun has an obvious quasi-11-year cycle and numerous short-term eruptive activities. From the aspect of energy, there are four processes of energy transmission in the effectuation chain of solar forcing to the climate system: the solar energy input to the atmosphere, the atmospheric absorption to the input energy, the transformation of the absorbed energy to dynamic and thermodynamic responses in the atmosphere, and the coupling among all the layers affected by solar forcings. However, the four processes have not been discussed in their entirety. In this present paper, studies in recent decade on how the solar radiation varies during the solar cycle as well as the eruptions, and correspondingly how the terrestrial atmosphere absorbs the input solar energy are reviewed.